Chemically intuitive indices for charge‐transfer excitation based on SAC‐CI and TD‐DFT calculations. Issue 29 (26th August 2013) - Ehara, Masahiro; Fukuda, Ryoichi; Adamo, Carlo; Ciofini, Ilaria
<x xml:space="preserve">Abstract</x> A recently proposed charge‐transfer (CT) index and some related quantities aimed to the description of CT excitations in push–pull donor–acceptor model systems were computed in vacuum and in ethanol by the direct symmetry‐adapted cluster‐configuration interaction (SAC‐CI) method including solvent effects by means of the nonequilibrium state‐specific approach. The effects of both solvation and electron correlations on these quantities were found to be significant. The present results are also in line with previous time‐dependent (TD) density functional theory calculations and they demonstrate that SAC‐CI provides a description of the excitation character close to that of TD‐PBE0. Indeed, CT indices evaluated by the SAC‐CI and TD‐PBE0 would be useful in the field of materials chemistry, for the design and development of novel molecular materials. © 2013 Wiley Periodicals, Inc.